2016
DOI: 10.3727/096504016x14634208142987
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of CREB Promotes Cell Proliferation by Mediating G1/S Phase Transition in Hodgkin Lymphoma

Abstract: The cyclic-AMP response element-binding protein (CREB), a well-known nuclear transcription factor, has been shown to play an essential role in many cellular processes, including differentiation, cell survival, and cell proliferation, by regulating the expression of downstream genes. Recently, increased expression of CREB was frequently found in various tumors, indicating that CREB is implicated in the process of tumorigenesis. However, the effects of CREB on Hodgkin lymphoma (HL) remain unknown. To clarify the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…The features of CREB in Hodgkin lymphoma (HL) strongly support its role as a tumor suppressor gene that can decelerate cell proliferation by inhibiting the expression of several cell cycle-related genes [23]. In this study, we revealed that transcription factors CREB and c-Myc positively regulated human STING gene promoter.…”
Section: Resultsmentioning
confidence: 72%
“…The features of CREB in Hodgkin lymphoma (HL) strongly support its role as a tumor suppressor gene that can decelerate cell proliferation by inhibiting the expression of several cell cycle-related genes [23]. In this study, we revealed that transcription factors CREB and c-Myc positively regulated human STING gene promoter.…”
Section: Resultsmentioning
confidence: 72%
“…However, in Hodgkin lymphoma, CREB1 was found to be tumor suppressive by regulating key aspects of cell proliferation. The authors showed that CREB1 depletion induces the expression of cell-cycle related genes and accelerates G1/S phase transition which in turn supports oncogenesis 48 .…”
Section: Discussionmentioning
confidence: 95%
“…Mutation of the Ser133 site to alanine in the endogenous CREB gene exerts a significant impact on CREB target genes in response to MSK1 activating stimuli [ 23 , 44 ]. Several studies have highlighted the important role of CREB in tumor progression and implicated its role in acute myeloid leukemia [ 45 ], acute lymphoblastic leukemia [ 46 , 47 ], myelomonocytic leukemia [ 48 ], Hodgkin lymphoma [ 49 ] and non-small cell lung cancer [ 50 , 51 ]. Here, we also found the upregulation of p-CREB in uveal melanoma tissues, indicating its role in tumor progression.…”
Section: Discussionmentioning
confidence: 99%